Desarrollo de una propuesta algorítmica para el estudio de la naturaleza del nódulo mamario - Cluzet, Oscar; Perrier, José Pedro; Cordero, Miguel; Chevalier, Nelma; Müller, Augusto; Risi, Leonardo; Delgado, Bolívar (Cirugía del Uruguay, 1990)
The author develops an algorithm designed for the study of the nature of mammary nodules in our country. lt is based on the c/inical aspects, mammography, cytology, and extemporaneous and definitive histology in 227 patients. The algorithm was evaluated for efficiency indicators and diagnostic capacity, as we/1 as statistic sensitivity.